Capacidade adaptativa dos estabelecimentos agropecuários nos municípios do semiárido brasileiro: uma análise a partir da disponibilidade de capitais - Silva, Eduarda Maria Farias (2022)
After successive drought events spread over decades, the population living in the Brazilian semi-arid region is still dealing with the effects of climate change. Actions aimed at mitigating the impacts caused by water scarcity are not enough to solve the problem. This fact demonstrates the low internalization of the concept of living with drought, as well as the weak adaptive capacity to climate change in agricultural establishments. In an attempt to reverse this situation, it is necessary to understand the local conditions and needs in terms of the population's ability to face droughts, especially the rural population. In this sense, the present study aims to characterize agricultural establishments in the municipalities of the Brazilian semiarid region in terms of their adaptive capacity to droughts. For this, indicators extracted from the 2017 Agricultural Census, published by the IBGE, were used. Adaptive capacity was studied based on the availability of social, human, economic and natural capital. The analysis methods adopted involved descriptive statistics techniques, factor analysis, via the principal components method, and construction of aggregate indices. Subsequently, Cluster analysis was used in order to group the municipalities into three different levels of adaptive capacity: lower, intermediate and higher levels. The results showed that the most important indicators to explain adaptive capacity were schooling and access to information, agricultural production management, existence and preservation of green areas and access to water. Regarding the classification of municipalities according to the adaptive capacity of their agricultural establishments, it was observed that 33.7% are among those with the lowest level of adaptive capacity, 43.4% in the intermediate level. The states of Ceará and Piauí presented the highest percentage of municipalities in the class with the lowest adaptive capacity. The overall average for the Adaptive Ability Index was just 0.284. The municipality of Messias Targino (RN) reached the highest value, with 0.444 and Belo Monte (AL) the lowest, with 0.160. The construction of the Adaptive Capacity Index for agricultural establishments in municipalities in the Brazilian semiarid region proved to be relevant when identifying that their adaptive capacity to climate change is manifested in a heterogeneous way, varying throughout the region.